2014
DOI: 10.1111/sed.12159
|View full text |Cite
|
Sign up to set email alerts
|

Mapping bathymetry and depositional facies on Great Bahama Bank

Abstract: Satellite imagery and an extensive set of water-depth measurements have been used to map and critically evaluate the magnitude and patterns of bathymetry across Great Bahama Bank. Descriptions of previously collected sediment samples were combined with satellite imagery to map and refine the interpreted distribution of surficial carbonate sediments (depositional facies). Data reveal that 60% of Great Bahama Bank lies in 5 m or less of water. The deep portion occurs mainly in a generally east-west trending area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(139 citation statements)
references
References 47 publications
10
129
0
Order By: Relevance
“…This is similar to the shallow subtidal lagoon protected by oolitic shoals in the Great Bahama Bank in which mud and pellet facies-belts are complexly distributed (e.g. Purdy, 1963;Halley et al, 1983;Reijmer et al, 2009;Harris et al, 2015). In fact, in the lagoon of the Great Bahama Bank the percentage of mud increases towards the coast of Andros Island (e.g.…”
Section: Interpretation Of Facies Association Bmentioning
confidence: 70%
See 2 more Smart Citations
“…This is similar to the shallow subtidal lagoon protected by oolitic shoals in the Great Bahama Bank in which mud and pellet facies-belts are complexly distributed (e.g. Purdy, 1963;Halley et al, 1983;Reijmer et al, 2009;Harris et al, 2015). In fact, in the lagoon of the Great Bahama Bank the percentage of mud increases towards the coast of Andros Island (e.g.…”
Section: Interpretation Of Facies Association Bmentioning
confidence: 70%
“…Wilkinson and Drummond, 2004;Suarez-Gonzalez et al, 2015), as it has been reported in numerous modern systems, such as Bahamas (e.g. Bathurst, 1975;Reijmer et al, 2009;Kaczmareck et al, 2010;Harris et al, 2015), Persian Gulf (e.g. Wagner and Van der Togt, 1973;Wilkinson and Drummond, 2004), Antigua (e.g.…”
Section: Depositional System and Evolution Of The Studied Units In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the protocol of Purkis et al (2014a) and Harris et al (2014), the slices were analysed using eCognition (v. 8.9, Trimble Inc.). By applying textural and edge-detection routines, refined by manual-editing, the polygonal buildup -ridges‖ and intra-buildup -ponds‖ were mapped and exported as GIS vector files for further analysis (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These facies, are characterized by enveloped grains, peloids and greater amount of micrite, related to lower energy sites. In terms of depositional energy, these sediments are equivalent to Andros Island rudstones and mud-poor packstones from Harris et al (2015), which were interpreted as deposited in water depths ranging from 5 to 10 feet deep. These interbank regions can be compared to deposits of sandy peloidais sheets of inner platform defined by Spadini (1992), interpreted as the product of variations in depositional energy between the bank crests.…”
Section: Depositional Modelmentioning
confidence: 99%